The Effectiveness of Mental Health Literacy Improvement in Reducing Stigma on Mental Health Service Users in Indonesia - Dewi Andira Wahyudi (Psycho Holistic, 2021)
Mental health is one of the most important things in human life. However, the prevalence of mental health problems in Indonesia is still quite high. Thus, mental health services need to be optimized in order to reduce this prevalence. But, in its implementation, the use of mental health services has not been maximized because of the stigma against people with mental disorders that are obtained from themselves and the social environment. Many people still think that people with mental health problems are insane, possessed, or lack of religious knowledge. This happens because of the lack of knowledge from the community itself. Thus, education and literacy regarding mental health are still very much needed in Indonesia, because those are one of the factors that influence a person's intention to seek professional help related to mental health problems. Our research will discuss how effective increasing mental health literacy is in reducing stigma among mental health service users in Indonesia. This research will be conducted with a literature study approach with data collection techniques called documentation and using content analysis methods. This research found that mental health literacy has an effect on reducing social and self-stigma among mental health service users.